2022
DOI: 10.1096/fj.202101647rr
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 shapes both the trophoblast invasion and decidual macrophage differentiation in early pregnancy

Abstract: Trophoblasts play critical roles in establishment and maintenance of a normal pregnancy. Their dysfunction in early pregnancy is closely related to pregnancy‐related diseases, including recurrent pregnancy loss (RPL). Epigenetic modifications dynamically change during pregnancy; however, the role of the epigenetic modifier UHRF1 in trophoblast regulation remains unknown. This is the first study to show that UHRF1 expression was localized in the cytoplasm of cytotrophoblasts, syncytiotrophoblasts, and villi col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…There are pieces of evidence that DNA methyltransferases (DNMTs) have a specific effect on the formation of macrophage phenotypes. Ubiquitin-like protein containing plant homeodomain (PHD) and RING finger domain 1 (UHRF1) maintains the DNA methylation status by recruiting DNMT1 ( 80 ). A recent study found that decreased UHRF1 in trophoblasts promotes the expression of pro-inflammatory IL-1β, which recruits monocytes to decidua and shifts them into the M1 phenotype, further exacerbating RPL ( 80 ).…”
Section: Factors Regulating Macrophage Phenotype and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are pieces of evidence that DNA methyltransferases (DNMTs) have a specific effect on the formation of macrophage phenotypes. Ubiquitin-like protein containing plant homeodomain (PHD) and RING finger domain 1 (UHRF1) maintains the DNA methylation status by recruiting DNMT1 ( 80 ). A recent study found that decreased UHRF1 in trophoblasts promotes the expression of pro-inflammatory IL-1β, which recruits monocytes to decidua and shifts them into the M1 phenotype, further exacerbating RPL ( 80 ).…”
Section: Factors Regulating Macrophage Phenotype and Functionmentioning
confidence: 99%
“…Ubiquitin-like protein containing plant homeodomain (PHD) and RING finger domain 1 (UHRF1) maintains the DNA methylation status by recruiting DNMT1 ( 80 ). A recent study found that decreased UHRF1 in trophoblasts promotes the expression of pro-inflammatory IL-1β, which recruits monocytes to decidua and shifts them into the M1 phenotype, further exacerbating RPL ( 80 ). In cancer, DNA methylation is critical for the suppression of the expression of tumor suppressor genes, whereas the loss of DNA methylation mediated by removal of methyl groups leads to the overexpression of oncogenes.…”
Section: Factors Regulating Macrophage Phenotype and Functionmentioning
confidence: 99%
“…Decidualized stroma 2 cells co-expressed markers of the pre-decidual and decidual states, EGR1 and CXCL2 (25,26), respectively. Decidualized stroma 3 cells were characterized by well-known decidualization markers such as IGFBP1 and TIMP3 (27), ATF3 (28), and transcription factors that are associated with late decidualization, including CSRNP1 (3).…”
Section: Endometrial Cell Type-specific Differentiation Defects In Fo...mentioning
confidence: 99%
“…UHRF1, which shapes M1 to M2 decidual macrophage differentiation in early pregnancy, is decreased in patients with recurrent pregnancy loss, resulting in increased cytokines such as CXCL2. This leads to the recruitment of monocytes and promotes the polarization to the M1 phenotype 85 …”
Section: Introductionmentioning
confidence: 99%